Influence of stroke coordinators on delivery of acute stroke care and hospital outcomes: An observational study. Issue 6 (August 2018) - Purvis, Tara; Kilkenny, Monique F; Middleton, Sandy; Cadilhac, Dominique A
Background: Stroke coordinators have been inconsistently used in various countries to support stroke care in hospital. Aim: To investigate the association between stroke coordinators and the provision of evidence-based care and patient outcomes in hospitals with acute stroke units. Methods: Observational study using cross-sectional data from the 2015 National Acute Services Audit Program (Australia): including a retrospective medical record audit (40 records from each hospital) and a self-reported survey of organizational resources for stroke. Multilevel random effects logistic regression for patient outcomes including complications, independence on discharge, and death. Median regression for length of stay comparisons. Results: A total of 109 hospitals submitted 4060 cases; 59 (54%) had a stroke coordinator. Compared with patients from stroke unit hospitals with no stroke coordinator ( N  = 33, 1333 cases), patients in stroke unit hospitals with a stroke coordinator ( N  = 53, 2072 cases) were more likely to receive clinical practices including rehabilitation therapy within 48 hours of initial assessment (88 vs. 82%, p  < 0.001), risk factor modification advice (62 vs. 55%, p  = 0.003) and receive a discharge care plan (65 vs. 48%, p  < 0.001). No differences in complications, independence on discharge, or deaths were evident. Patients from hospitals with a stroke coordinator were more likely to access inpatient rehabilitation (adjusted odds ratio 1.8, 95% confidence interval 1.1–2.8) and have a reduced length of acute stay if discharged (median 14 h, p  = 0.03). Conclusion: Presence of stroke coordinators was associated with reduced length of stay and improved delivery of evidence-based care in hospitals with a stroke unit.